2013
DOI: 10.5923/j.sports.20120205.02
|View full text |Cite
|
Sign up to set email alerts
|

Thriving in the Challenge of Geographical Dislocation: A Case Study of Elite Australian Footballers

Abstract: Young adult athletes are often required to relocate as part of their career progression. The transition between their 'old' and 'new' lives can have a positive or negative effect on their future career. The purpose of this study was to identify the processes and characteristics of thriv ing in periods of geographical d islocation; particularly the move away fro m the 'familiar' to the 'unfamiliar'. A partially mixed, sequential design was employed, in itially to identify the indiv idualities of a group of 24 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…3 Literature on thriving in sport has begun to identify the psychosocial variables important for understanding why some performers thrive whereas others do not. For example, exhibiting a readiness for challenge was shown to enable thriving during a geographic transition, 5 and operating within an integrated, inclusive, and trusting environment was suggested to facilitate thriving within a professional team sport. 6 To explain these associations and understand how these factors influence thriving, it is necessary to examine the mechanistic variables at play (i.e., the proximal determinants of thriving).…”
Section: Introductionmentioning
confidence: 99%
“…3 Literature on thriving in sport has begun to identify the psychosocial variables important for understanding why some performers thrive whereas others do not. For example, exhibiting a readiness for challenge was shown to enable thriving during a geographic transition, 5 and operating within an integrated, inclusive, and trusting environment was suggested to facilitate thriving within a professional team sport. 6 To explain these associations and understand how these factors influence thriving, it is necessary to examine the mechanistic variables at play (i.e., the proximal determinants of thriving).…”
Section: Introductionmentioning
confidence: 99%
“…When considering the role that environmental factors play in promoting thriving in sport, it will be important to recognize that variations exist in the nature of settings (e.g., clubs at different competition standards). For example, when relocating as part of earning a professional contract with a club, a young player will move from a familiar setting where he or she will have established support networks to one where he or she may need to create and access new social connections in order to thrive (Harris, Myhill, & Walker, 2012a, 2012b.…”
Section: Sports Performers' Perspectives On Facilitating Thriving In mentioning
confidence: 99%
“…Examples of personal enablers of thriving in sport have included desire and motivation, goal setting and creating challenge, positive mental state, self-belief, mental toughness, self-regulation, and personal resilient qualities ( Brown et al, 2017b , 2018 ; Gucciardi et al, 2017 ; McNeill et al, 2018 ). Turning to contextual enablers, these have included the depth and sincerity of relationships and the support that can be provided by coaches, support staff, parents, and colleagues/teammates ( Harris et al, 2012 ; Brown et al, 2017b ; Gucciardi et al, 2017 ; Brown and Arnold, 2019 ). Further research is, however, required on the relationship between contextual enablers and thriving in sport, given that Brown et al (2017b) contrastingly found that perceived social support, coach need support, and coach need thwart variables could not significantly predict sport performers’ membership to a thriving profile.…”
Section: Introductionmentioning
confidence: 99%